2016
DOI: 10.1139/cjfas-2015-0312
|View full text |Cite
|
Sign up to set email alerts
|

Can recovery from disturbance explain observed declines in total phosphorus in Precambrian Shield catchments?

Abstract: The plausibility of land disturbance as a cause of declining phosphorus (P) concentrations in oligotrophic lakes within south-central Ontario, Canada, is evaluated using the process-based model INCA-P. The model was calibrated upon three catchments in the Muskoka–Haliburton region (MHR): Harp (HP), Dickie (DE), and Plastic (PC), which have varying degrees of declining P export and different forms of historic disturbances (timber harvesting, tree death, and soil acidification, respectively). Hindcasts (1978–200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Further analysis over a longer monitoring period is required to understand the effects of warm winters on TP lake ; however, if this is important, it suggests that TP lake in northern lakes may be expected to decline with continued climate warming. Several previous studies have observed declining TP in forested boreal catchments in North America and Europe (Arvola et al, ; Crossman et al, ; Eimers et al, ; Huser et al, ; Stammler et al, ), suggesting that the patterns observed in Sweden may be broadly relevant, although contrasting patterns have been observed in the United States (excluding Alaska and Hawaii) where TP in lakes and streams in relatively undisturbed catchments has increased in recent years (Stoddard et al, ).…”
Section: Discussionmentioning
confidence: 94%
“…Further analysis over a longer monitoring period is required to understand the effects of warm winters on TP lake ; however, if this is important, it suggests that TP lake in northern lakes may be expected to decline with continued climate warming. Several previous studies have observed declining TP in forested boreal catchments in North America and Europe (Arvola et al, ; Crossman et al, ; Eimers et al, ; Huser et al, ; Stammler et al, ), suggesting that the patterns observed in Sweden may be broadly relevant, although contrasting patterns have been observed in the United States (excluding Alaska and Hawaii) where TP in lakes and streams in relatively undisturbed catchments has increased in recent years (Stoddard et al, ).…”
Section: Discussionmentioning
confidence: 94%
“…Deposition and weathering of P-containing minerals are two non-wetland sources of inorganic P; deposition is relatively constant across the region, but localised pockets of apatite may result in differences in Pweathering amongst catchments (Casson, Eimers, & Watmough, 2012;Eimers et al, 2009;O'Brien et al, 2013). Furthermore, P export from these catchments is very sensitive to forest and wetland disturbance, which may complicate the observed relationships with wetland proportion (Crossman et al, 2016;Pinder, Eimers, & Watmough, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…, Crossman et al. ). Limited research, however, focuses on incorporating the influence of terrestrial features on the biological recovery of lakes from disturbance, and how these factors might vary across spatial and temporal scales.…”
Section: Introductionmentioning
confidence: 99%
“…Since a large proportion of the world's human population lives in regions with high threats to water security and biodiversity, understanding factors leading to freshwater resilience, damage, and recovery should be a management priority (Strayer andDudgeon 2010, V€ or€ osmarty et al 2010). In lakes that have experienced severe chemical or catchment disturbance, recovery assessments traditionally occur at single scales of regional and catchment levels (Keller et al 2007, Garmo et al 2014, Ginn et al 2015, Crossman et al 2016. Limited research, however, focuses on incorporating the influence of terrestrial features on the biological recovery of lakes from disturbance, and how these factors might vary across spatial and temporal scales.…”
Section: Introductionmentioning
confidence: 99%